The Role of the Diversity of the Board of Directors in Promoting Integrated Disclosure and Social Responsibility - Gatea, Ali Khalaf; Jarad, Haider Ali (Technium Sustainability, 2021)
The integrated Disclosure aims to provide a comprehensive picture of the performance of the organization, and because the quality of the Disclosure is a critical aspect of the integrated reports, so the research aims to show the impact of the diversity of the board of directors on the quality of the integrated reports and the promotion of the social responsibility of the organization, and to make decisions about disclosure and integration in the information provided in order to benefit from it In building integrated visions about the organization, assuming that the diversity of the board of directors has a significant relationship to the extent to which the quality of integrated Disclosure is achieved, that the most important findings of the research stipulate that the diversity of the board of directors contributes to social responsibility and integrated disclosure, and the strengthening of organizational culture and administrative practices, and the research recommends, The need to interact with the environment and the communities in which the organization operates, to enable it to provide environmental, social or ethical information, along with financial, strategic and governance information in an annual report. Key word: Diversity, Integrated Disclosure, Social Responsibility. Youtube link: https://www.youtube.com/watch?v=Fy7prErVc3w